Investments As a Factor of Growth of Economic Indicators - Akhmedov Rakhmonjon Mamadjonovich (Genius Journals, 2022)
This article discusses the role of investment in the development of economic indicators. The types of investments, their significance and role in the economy of the region are analyzed
Keywords: Economy; macroeconomics; analysis; investments